(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we propose an ordinary differential equation model with logistic target cell growth to describe influence of raltegravir intensification on viral dynamics. The basic reproduction number R_0 is established. The infection-free equilibrium E_0 is globally attractive if R_0 < 1, while virus is uniformly persistent if R_0 > 1. In addition, we find that Hopf bifurcation can occur at around the positive equilibrium within certain parameter ranges. Numerical simulations are performed to illustrate theoretical results.